Preparation method and application of built-in electric field of carbon dinitrogen-regulated gold-doped graphite phase carbon nitride

By regulating the preparation of gold-doped graphite phase carbon nitride, the size and structural limitations of graphite phase carbon nitride in the field of photocatalysis are solved, the formation of porous structure and strong internal electric field is achieved, and visible photocatalysis is significantly improved The properties of degraded RhB and the stability of the catalyst.

CN119140146AInactive Publication Date: 2024-12-17NANJING COLLEGE OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350919.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Graphite phase carbon nitride (g-C3N4) has problems such as large size, easy agglomeration, small specific surface area, low quantum efficiency, small light absorption range and low photogenerated carrier recombination rate in the field of photocatalytics, which limits its application potential. Moreover, the defects in the traditional heterojunction interface structure are not conducive to the improvement of photocatalytic reaction efficiency.

Method used

The preparation method of carbon nitride of gold-doped graphite phase is used to regulate carbon nitride by carbon dioxide, and the carbon dioxide aqueous solution is added to form carbon dioxide modification by heating and stirring in water. The gold-doped graphite phase carbon nitride has a porous sheet structure and a strong internal electric field to improve photocatalytic performance.

Benefits of technology

The specific surface area and active sites are significantly increased, the light absorption utilization rate and photogenerated carrier separation efficiency are enhanced, and the performance of visible light catalytic degradation of RhB and the cyclic stability of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140146A_ABST
    Figure CN119140146A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a built-in electric field of carbon dinitrogen-regulated gold-doped graphite phase carbon nitride. According to the material, under the condition of a weakly alkaline water solvent, generated amino ureide is coordinated and complexed with metal ions, and then a metal-doped supramolecular precursor is generated with melamine and cyanuric acid through intermolecular hydrogen-bond interaction and charge mutual attraction interaction; the gold-doped graphite phase carbon nitride is further conjugated and stacked with carbon dinitrogen pi-pi to form a carbon dinitrogen composite metal-doped supramolecular precursor, and finally, the carbon dinitrogen modified gold-doped graphite phase carbon nitride is prepared through high-temperature etching. The prepared modified graphite-phase carbon nitride is of a porous lamellar structure, the specific surface area of the modified graphite-phase carbon nitride is greatly increased, and the modified graphite-phase carbon nitride has more active sites; meanwhile, the energy band structure is regulated and controlled through gold ion doping, and the light absorption and utilization rate is increased; besides, the surface of positively charged gold-doped graphite phase carbon nitride is coupled with the surface of negatively charged carbon dinitrogen to form a strong potential point, so that a stronger built-in electric field is promoted, and the separation efficiency of photon-generated carriers is improved, thereby greatly improving the visible light catalytic degradation activity of original carbon nitride on rhodamine B.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a preparation method and application of carbon dinitrogen for regulating the built-in electric field of gold-doped graphite phase carbon nitride, belonging to the field of nano material preparation. Background Art

[0002] In the past century, human society has developed rapidly, and fossil fuel resources have been consumed seriously, resulting in immeasurable resource shortages and environmental pollution. Finding clean, renewable green energy has become an urgent task for the world. The new semiconductor photocatalytic technology is a green technology that uses semiconductors to convert solar energy into high-energy chemical energy. It has great application prospects in the fields of renewable clean energy production and pollutant remediation.

[0003] Graphitic carbon nitride (g-C3N4), as a two-dimensional layered material formed by sp² hybridization of C and N elements, has great application potential in photocatalysis, electrocatalysis, energy storage and other fields due to its unique electronic structure, excellent chemical stability and thermal stability. However, the g-C3N4 prepared by high-temperature thermal polycondensation reaction has large size, easy agglomeration, small specific surface area, low quantum efficiency, small light absorption range, and high photogenerated carrier recombination rate, which seriously limit its application. In recent years, with the rapid development of nanotechnology and materials science, researchers have continuously explored the modification methods of g-C3N4 in order to further improve its performance and broaden its application range. The built-in electric field is the electric field generated by the uneven distribution of charges in different regions of semiconductor materials, which has an important influence on the electronic transport and catalytic performance of the material. By regulating the built-in electric field of g-C3N4, its catalytic performance can be further optimized and the reaction efficiency can be improved. Yang et al. used alkali metal salts (KCl+NaCl) to assist in the co-thermal polymerization of multiple precursors (melamine+thiourea+urea) to achieve the construction of structural undulations (i.e., the potential difference generated) within the conjugated plane of g-C3N4 to induce a directional strong built-in electric field, and constructed a multi-level structural unit g-C3N4 intermolecular homojunction, thereby greatly improving its photocatalytic hydrogen production efficiency. (Yang H, Sun S, Lyu J, YangQ&Cui, J. Mechanism insight into triple S-Schemeintermolecular carbon nitride homojunction with robust built-inelectric field for highly enhanced photocatalytic hydrogenevolution[J].Chemical Engineering Journal, 2024, 481, 148297.) Although studies have shown that the built-in electric field can significantly promote the exciton dissociation and separation and transfer of electron-hole pairs of g-C3N4 to enhance the photocatalytic performance, the large number of structural defects in the interface region of the traditional heterojunction often become the recombination center of photogenerated carriers, which is still not conducive to the improvement of the efficiency of the photocatalytic reaction. Carbon dinitrogen (C2N) has aroused great interest among researchers due to its uniform porous nitridation structure and wide band gap, and the application of C2N has been fully studied. Wang et al. achieved overall water splitting using visible light by constructing a heterostructure composed of azo-fused microporous polymers and C2N ultrathin nanosheets.(Wang L, Zheng X, Chen L. Xiong Y&Xu H. Van der Waals Heterostructures Comprised of Ultrathin Polymer Nanosheets for Efficient Z-Scheme Overall Water Splitting. Angewandte Chemie, 2018, 57, 3454-3458.) Since two-dimensional C2N and g-C3N4 have similar layered structures, but the surface potentials between the two are different, the composite material can locally form a double-layer structure, promote a stronger internal electric field, and improve the volume charge separation efficiency of the material, thereby greatly improving its photocatalytic efficiency. Therefore, the preparation method of carbon dinitrogen regulating the built-in electric field of gold-doped graphite phase carbon nitride reported in this article has great practical significance and prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a carbon dinitrogen-regulated gold-doped graphite phase carbon nitride built-in electric field, wherein the material has excellent visible light catalytic degradation performance of RhB.

[0005] The technical solution to achieve the purpose of the present invention is: a preparation method for carbon dinitrogen regulating the built-in electric field of gold-doped graphite phase carbon nitride, comprising the following steps: The first step is to disperse urea, melamine, cyanuric acid and gold ions in water, and heat and stir; The second step is to slowly drop the carbon dinitrogen aqueous solution into the mixed solution prepared in the first step, and heat and stir; Step 3: Pour the mixed solution obtained in step 2 into the reaction kettle while it is still hot, perform hydrothermal reaction at 120±10°C, and then cool to room temperature; The fourth step is to wash the solid obtained from the reaction in the third step several times and then dry it to obtain a carbon dinitrogen composite metal doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10° C. to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride.

[0006] Furthermore, in the first step, the mass ratio of urea, melamine and cyanuric acid is 1:1:1, the gold ion compound is tetrachloroauric acid, and the mass ratio of gold ions to melamine is 5:1000-25:1000.

[0007] Furthermore, in the first step, the heating and stirring temperature is 60-80 °C, and the stirring time is 2-4 h.

[0008] Furthermore, in the second step, the mass ratio of carbon dinitrogen to melamine is 1:400.

[0009] Furthermore, in the third step, the hydrothermal reaction time is 8 to 16 h.

[0010] Furthermore, in the fifth step, the calcination time is 2-4 h.

[0011] The carbon dinitrogen modified gold-doped graphite phase carbon nitride prepared by the above method is used as a catalyst for the visible light photocatalytic degradation of rhodamine B.

[0012] Compared with the prior art, the advantages of the present invention are: (1) the carbon dinitrogen modified gold-doped graphite phase carbon nitride prepared by the present invention has a porous thin sheet structure, which greatly increases its specific surface area and has more active sites, thereby increasing the possibility of its photocarriers participating in photocatalysis and shortening its diffusion length; (2) the doping of an appropriate amount of gold ions can effectively adjust its energy band structure and enhance the light absorption utilization rate; (3) the positively charged gold-doped graphite phase carbon nitride surface is coupled with the negatively charged carbon dinitrogen surface to form a strong potential point, forming a stronger internal electric field, thereby improving the separation efficiency of its photogenerated carriers, and thus facilitating the improvement of the performance of the catalyst in the visible light catalytic degradation of rhodamine B. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a transmission electron microscope image of the comparative case g-C3N4 (a) of the present invention and ACN-10 (b) prepared in Example 2.

[0014] Figure 2 1 is the Fourier transform infrared spectra of the comparative case g-C3N4 (a) of the present invention and ACN-10 prepared in Example 2 (b).

[0015] Figure 3 It is the XRD diffraction spectrum of the modified graphite phase carbon nitride prepared by the comparative case g-C3N4 and Examples 1-5 of the present invention.

[0016] Figure 4 The performance degradation diagram (a) and pseudo-first-order kinetic reaction curve (b) of the photocatalytic degradation of RhB by the modified graphite phase carbon nitride prepared in the comparative example and examples 1-5 of the present invention.

[0017] Figure 5 This is a cyclic stability diagram of the photocatalytic degradation of Rhodamine B using ACN-10 prepared in Example 2 of the present invention as a catalyst. DETAILED DESCRIPTION

[0018] The preparation steps of carbon dinitrogen modified gold-doped graphite phase carbon nitride and the visible light photocatalytic degradation process of rhodamine B of the present invention are as follows: In the first step, urea, melamine, cyanuric acid and gold ions are dispersed in deionized water and heated and stirred at 60-80 °C for 2-4 h. The second step is to slowly drop the carbon dinitrogen aqueous solution into the mixed solution prepared in the first step, and heat and stir; Step 3: Pour the mixed solution obtained in step 2 into the reactor while it is still hot, perform hydrothermal reaction at 120±10℃ for 8-16 hours, and then cool to room temperature; The fourth step is to wash the solid obtained from the third step reaction for multiple times and then dry it at 60°C to obtain a carbon dinitrogen complex metal-doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10°C for 2-4 h to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride.

[0019] In the sixth step, 5 mg of the prepared graphite phase carbon nitride was weighed into a photocatalytic tube, and the dye rhodamine B (RhB) was added, stirred in a dark room for 30 min, and reacted under visible light.

[0020] Embodiment 1: In the first step, 1 g urea, 1 g melamine, 1 g cyanuric acid and tetrachloroauric acid (gold ion content 5 mg) were dispersed in 70 mL water and heated at 60 °C with stirring for 2 h. In the second step, 10 mL of carbon dinitrogen aqueous solution (2.5 mg mL -1 ) was slowly dripped into the mixed solution prepared in the first step, and heated and stirred for 30 min; Step 3: Pour the mixed solution obtained in step 2 into the reactor while it is still hot, perform hydrothermal reaction at 120 °C for 8 h, and then cool to room temperature; The fourth step is to wash the solid obtained from the third step reaction for multiple times and then dry it at 60°C to obtain a carbon dinitrogen complex metal-doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10°C for 2 h to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride ACN-5.

[0021] Step 6: Weigh 5 mg of ACN-5 into a photocatalytic tube, add the dye rhodamine B (RhB), stir in a dark room for 30 min, and react under visible light.

[0022] The results are as follows Figure 4 As shown in Figure 2, when RhB was degraded under visible light, its degradation rate reached 0.00687 min -1 .

[0023] Embodiment 2: In the first step, 1 g of urea, 1 g of melamine, 1 g of cyanuric acid and tetrachloroauric acid (gold ion content 10 mg) were dispersed in 70 mL of water and heated at 80 °C with stirring for 2 h. In the second step, 10 mL of carbon dinitrogen aqueous solution (2.5 mg mL -1 ) was slowly dripped into the mixed solution prepared in the first step, and heated and stirred for 30 min; Step 3: Pour the mixed solution obtained in step 2 into the reactor while it is still hot, perform hydrothermal reaction at 120 °C for 12 h, and then cool to room temperature; The fourth step is to wash the solid obtained from the third step reaction for multiple times and then dry it at 60°C to obtain a carbon dinitrogen complex metal-doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10°C for 4 h to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride ACN-10.

[0024] Step 6: Weigh 5 mg into a photocatalytic tube, add the dye rhodamine B (RhB), stir in a dark room for 30 min, and react under visible light.

[0025] The prepared ACN-10 was characterized by transmission electron microscopy, Fourier transform infrared spectroscopy and XRD diffraction spectrum. Figure 1-3 shown.

[0026] The prepared graphite phase carbon nitride was used as a visible light photocatalyst to test the photocatalytic degradation of RhB. Figure 4 As shown in Figure 2, compared with other graphene-based carbon nitrides, this ACN-10 has the best visible light photocatalytic performance. When degrading RhB dye under visible light, its degradation rate is 0.02049 min -1 . And if Figure 5 As shown, the prepared ACN-10 has good cyclic stability as a catalyst for photocatalytic degradation of RhB.

[0027] Embodiment 3: In the first step, 1 g urea, 1 g melamine, 1 g cyanuric acid and tetrachloroauric acid (gold ion content 15 mg) were dispersed in 70 mL water and heated at 80 °C with stirring for 4 h. In the second step, 10 mL of carbon dinitrogen aqueous solution (2.5 mg mL -1 ) was slowly dripped into the mixed solution prepared in the first step, and heated and stirred for 30 min; Step 3: Pour the mixed solution obtained in step 2 into the reactor while it is still hot, perform hydrothermal reaction at 120 °C for 12 h, and then cool to room temperature; The fourth step is to wash the solid obtained from the third step reaction for multiple times and then dry it at 60°C to obtain a carbon dinitrogen complex metal-doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10°C for 4 h to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride ACN-15.

[0028] Step 6: Weigh 5 mg of ACN-15 into a photocatalytic tube, add the dye rhodamine B (RhB), stir in a dark room for 30 min, and react under visible light.

[0029] The results are as follows Figure 4 As shown in Figure 2, when RhB is degraded under visible light, its degradation rate is 0.01215 min -1 .

[0030] Embodiment 4: In the first step, 1 g of urea, 1 g of melamine, 1 g of cyanuric acid and tetrachloroauric acid (gold ion content 20 mg) were dispersed in 70 mL of water and heated at 60 °C with stirring for 4 h. In the second step, 10 mL of carbon dinitrogen aqueous solution (2.5 mg mL -1 ) was slowly dripped into the mixed solution prepared in the first step, and heated and stirred for 30 min; Step 3: Pour the mixed solution obtained in step 2 into the reactor while it is still hot, perform hydrothermal reaction at 120 °C for 16 h, and then cool to room temperature; The fourth step is to wash the solid obtained from the third step reaction for multiple times and then dry it at 60°C to obtain a carbon dinitrogen complex metal-doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10°C for 4 h to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride ACN-20.

[0031] Step 6: Weigh 5 mg of ACN-20 into a photocatalytic tube, add the dye rhodamine B (RhB), stir in a dark room for 30 min, and react under visible light.

[0032] The results are as follows Figure 4 As shown in Figure 2, when RhB was degraded under visible light, its degradation rate reached 0.0095 min -1 .

[0033] Embodiment 5: In the first step, 1 g of urea, 1 g of melamine, 1 g of cyanuric acid and tetrachloroauric acid (gold ion content 25 mg) were dispersed in 70 mL of water and heated at 60 °C with stirring for 2 h. In the second step, 10 mL of carbon dinitrogen aqueous solution (2.5 mg mL -1 ) was slowly dripped into the mixed solution prepared in the first step, and heated and stirred for 30 min; Step 3: Pour the mixed solution obtained in step 2 into the reactor while it is still hot, perform hydrothermal reaction at 120 °C for 16 h, and then cool to room temperature; The fourth step is to wash the solid obtained from the third step reaction for multiple times and then dry it at 60°C to obtain a carbon dinitrogen complex metal-doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10°C for 4 h to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride ACN-25.

[0034] Step 6: Weigh 5 mg of ACN-25 into a photocatalytic tube, add the dye rhodamine B (RhB), stir in a dark room for 30 min, and react under visible light.

[0035] The results are as follows Figure 4 As shown in Figure 2, when RhB is degraded under visible light, its degradation rate is 0.0067 min -1 .

[0036] Comparison case: In the first step, 1 g urea, 1 g melamine, and 1 g cyanuric acid were dispersed in 70 mL water and heated at 60 °C with stirring for 2 h. In the second step, the mixed solution prepared in the first step was poured into the reactor while hot, and subjected to hydrothermal reaction at 120 °C for 8 h, and then cooled to room temperature; In the third step, the solid obtained from the second step reaction is washed several times and then dried at 60°C to obtain a precursor; In the fourth step, the precursor obtained in the third step is calcined at 550±10°C for 4 h to obtain the original graphite phase carbon nitride g-C3N4.

[0037] In the fifth step, 5 mg g-C3N4 was weighed into a photocatalytic tube, and the dye Rhodamine B (RhB) was added. The mixture was stirred in a dark room for 30 min and reacted under visible light.

[0038] The results are as follows Figure 4 As shown in Figure 2, when RhB is degraded under visible light, its degradation rate is 0.0066 min -1 .

[0039] The above embodiments are only preferred technical solutions of the present invention.

Claims

1. A preparation method and application of carbon dinitrogen to regulate the built-in electric field of gold-doped graphite phase carbon nitride, characterized in that: The steps include: The first step is to disperse urea, melamine, cyanuric acid and gold ions in water, and heat and stir; The second step is to slowly drop the carbon dinitrogen aqueous solution into the mixed solution prepared in the first step, and heat and stir; Step 3: Pour the mixed solution obtained in step 2 into the reaction kettle while it is still hot, perform hydrothermal reaction at 120±10°C, and then cool to room temperature; The fourth step is to wash the solid obtained from the reaction in the third step several times and then dry it to obtain a carbon dinitrogen composite metal doped supramolecular precursor; In the fifth step, the carbon dinitrogen composite metal-doped supramolecular precursor obtained in the fourth step is calcined at 550±10° C. to obtain carbon dinitrogen-modified gold-doped graphite phase carbon nitride.

2. The method according to claim 1, characterized in that In the first step, the mass ratio of urea, melamine and cyanuric acid is 1:1:1, the gold ion compound is tetrachloroauric acid, and the mass ratio of gold ions to melamine is 5:1000-25:1000.

3. The method according to claim 1, characterized in that In the first step, the heating and stirring temperature is 60-80 °C, and the stirring time is 2-4 h.

4. The method according to claim 1, characterized in that In the second step, the mass ratio of carbon dinitrogen to melamine is 1:

400.

5. The method according to claim 1, characterized in that In the third step, the hydrothermal reaction time is 8 to 16 h.

6. The method according to claim 1, characterized in that In the fifth step, the calcination time is 2-4 h.

7. The use of carbon dinitrogen modified gold-doped graphite phase carbon nitride prepared by the method according to any one of claims 1 to 5, characterized in that: It was used as a catalyst for visible light photocatalytic degradation of RhB.